An evaluation of a health screening program for migrant women to Taiwan, China. Issue 2 (1st April 2016) - Huang, Yu-Chu; Mathers, Nigel Joseph; Chia, Su-Lih; Shiu, Ming-Neng; Kao, Shu-Chen
Abstract : Objective: We aimed to evaluate an integrated screening program for female migrants to Taiwan. Method: We performed a mixed methodological evaluation of a public health nurse (PHN)-led intervention to promote an integrated screening program for female migrants to Taiwan. The clinical case yield was determined by an audit, and staff/client questionnaires were used for the evaluation. Screening comprised surveillance for four untreated chronic diseases (hypertension, diabetes mellitus, tuberculosis, and liver disease), four cancers (mouth, bowel, liver, and cervix), parasitic infection, and hyperlipidemia. Results: Three hundred and thirty-six PHNs and 4751 immigrant women – with an average age of 29.2 years, most of whom were from Vietnam (44%) or mainland China (41%) – took part in the programme. Two thirds of screened women had no abnormalities. Further investigation was required in 1523 women, of whom 1220 were found to have significant disease. The majority of 280 PHNs (85%) found the content, processes, and waiting time to be 'highly acceptable' and thought the program was worthwhile and could be incorporated into standard care. Conclusions: The Taipei County Comprehensive Health Screening Programme provided an accessible, free-of-charge, and preventative intervention for female migrants to Taiwan and had a good clinical case yield.